Gastrointestinal protozoa in pet cats from Anhui province: prevalence and molecular characterization - Hao Zhang; Xing Tong; Zhonghui Ma; Tao Zhang; Feng Wu; Qiong Wu; Congshan Yang; Chunyang Han (Frontiers in Cellular and Infection Microbiology)
IntroductionTo investigate the prevalence of Tritrichomonas foetus, Pentatrichomonas hominis, Giardia intestinalis, Cryptosporidium, Microsporidium, and Sarcocystis in domestic cats in Anhui Province, China, and their potential role as zoonotic hosts for human infection, a total of 304 fecal samples from two different sources were screened for the presence of related pathogens.MethodsUsing microscopy, along with polymerase chain reaction (PCR) or nested PCR amplification, followed by genotyping through sequence analysis.ResultsThe infection rates of T. foetus, P. hominis, G. intestinalis, Cryptosporidium, Enterocytozoon bieneusi, and Sarcocystis were 5.6%, 0%, 1.7%, 0.7%, 2.6%, and 0%, respectively. The evolutionary relationships and genetic characteristics of G. intestinalis based on the GDH gene, Cryptosporidium based on the SSU rRNA gene, and E. bieneusi based on the ITS sequence were assessed: five cases of G. intestinalis were identified, with four belonging to assemblage F and one to zoonotic assemblage B, two Cryptosporidium cases were identified as Cryptosporidium felis, and all eight E. bieneusi cases were identified as belonging to group 1, with three cases being genotype D, three EbpA, and two EbpC.DiscussionAge, neutering status, and deworming were identified as potential risk factors. Further analysis revealed that diarrhea, as a clinical symptom, could serve as an indicator for pathogen infection. Although the pathogen infection rates detected in this study were relatively low, their zoonotic transmission potential cannot be ignored. Therefore, special attention should be paid, and it is essential to establish targeted prevention plans.